Organizational behavior : emerging realities for the workplace revolution - 432779 McShane, Steven Lattimore; Von Glinow, Mary Ann Young, 1949- 297318 (New York : McGraw-Hill/Irwin, 2005)
Program Iskandar Puteri Rendah Karbon;